2023
DOI: 10.1093/plphys/kiad182
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA ppe-miR393 mediates auxin-induced peach fruit softening by promoting ethylene production

Abstract: Auxin can inhibit or promote fruit ripening, depending on the species. Melting flesh (MF) peach fruit (Prunus persica L. Batsch) cultivars produce high levels of ethylene caused by high concentrations of indole-3-acetic acid (IAA), which leads to rapid fruit softening at the late stage of development. In contrast, due to the low concentrations of IAA, the fruit of stony hard (SH) peach cultivars do not soften and produce little ethylene. Auxin seems necessary to trigger the biosynthesis of ethylene in peach fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 85 publications
0
0
0
Order By: Relevance
“…It is hypothesized that PslTIR1 positively regulates auxin response and fruit set by mediating the degradation of Aux/IAA proteins, especially IAA9. In peaches, lower TIR1 protein levels trigger the stabilization of PpIAA13, leading to the accumulation of PpIAA13 protein, thus activating the expression of PpACS1 and promoting peach fruit softening [21]. In this study, we analyzed the expression of some auxin response genes and cell wall metabolic genes related to fruit firmness by transiently overexpressing the PpTIR1 gene in peach fruit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesized that PslTIR1 positively regulates auxin response and fruit set by mediating the degradation of Aux/IAA proteins, especially IAA9. In peaches, lower TIR1 protein levels trigger the stabilization of PpIAA13, leading to the accumulation of PpIAA13 protein, thus activating the expression of PpACS1 and promoting peach fruit softening [21]. In this study, we analyzed the expression of some auxin response genes and cell wall metabolic genes related to fruit firmness by transiently overexpressing the PpTIR1 gene in peach fruit.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of the peach PpIAA19 (Ppa011935m) gene in tomatoes resulted in an increase in plant height, the number of lateral roots, and changes in parthenogenesis and fruit morphology [20]. The latest study showed that high levels of PpIAA13 (Ppa010871m) resulted in high expression of PpACS1, which increased ethylene production and peach fruit softening [21].…”
Section: Introductionmentioning
confidence: 99%